Indivisibility, fairness, farsightedness and their implications for security - S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper is concerned with the problems of achieving lasting peace. One dimension includes fairly sharing the post-war economic and political pie or the peace dividend. This requires post-war allocations that are envy free. Many peace agreements that end civil wars are notoriously unstable in that they are often not implemented, or break down after some time. Commitments to the peace treaty are simply not credible. One reason for that could be certain indivisibilities in perceived shares of power and income in the peace settlement, as well as the inability to correctly infer the value of path dependence when future reputation depends on present actions but the future is heavily discounted. The paper also discusses the role of another type of unfairness, namely a deep sense of humiliation, in determining acts of transnational terrorism, where force may not be the answer in attempting to deter deeply motivated persons.
Keywords: C78; D71; D74; O10; 330; fair division; commitment; peace treaties; terrorist motivation